Continuité et adaptation : Les priorités stratégiques du gouvernement de la France - Garigue, Philippe (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1991)
French strategic priorities have been marked since the Second World War by the need to maintain continuity in national identity while adapting to changing world conditions. This process has been successful because the French Government was able to achieve a « minimal » political consensus and prevent fondamental contradiction in goals from developing. It is now extending its priorities so as to achieve a new harmonization between national defence and the development of a European defence, while maintaining a role in the structuration of world security. However, the cost of defence is gradually demonstrating that a further adaptation is required, through the consolidation of European defence. Yet, while accepting some supranational transfers of competence, this adaptation is now raising the question of the capacity for the « minimal » consensus to be maintained while balancing national sovereignty against efficiency.